Part 2: Imaging findings of uncommon but important immune checkpoint inhibitor‐related adverse effects. Issue 4 (1st March 2022) - Noë, Geertje; Cardin, Anthony; Lasocki, Arian
Abstract: Oncology care has significantly changed with the emergence of immunotherapy agents, in particular immune checkpoint inhibitors (ICIs). This has had an immediate effect on imaging, with different radiological tumour responses to treatment compared with conventional chemotherapies, and novel imaging findings due to complications caused by these agents (referred to as immune‐related adverse effects, irAEs). Some of the more common irAEs may be familiar, but as the use of ICIs increases to a wider variety of cancers, these complications, and in particular, the less common irAEs, will be encountered more frequently on imaging. It will be increasingly important to be familiar with these uncommon irAEs, particularly since they can be difficult to recognise and distinguish from metastatic disease. The aim of this pictorial essay was to describe and illustrate imaging findings that may be encountered related to uncommon but important irAEs as a result of treatment with immune checkpoint inhibitors.